Graphene-Skeleton Heat-Coordinated and Nanoamorphous-Surface-State Controlled Pseudo-Negative-Photoconductivity of Tiny SnO₂ Nanoparticles - Ding, Longwei (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.